HUBUNGAN KECERDASAN EMOSIONAL DAN MOTIVASI DENGAN TINGKAT PRESTASI BELAJAR SISWA KELAS V MADRASAH IBTIDAIYAH NEGERI (MIN) JEJERAN BANTUL PADA MATA PELAJARAN BAHASA INDONESIA - Maksum, Khanif (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
This study tried to reveal the relationship between emotional intelligence and learning motivation, the relationship between learning motivation and students achievement, and to explain the direct and indirect relationships between emotional intelligence and learning motivation with the students achievement. In accordance with the theme, this study is a correlational quantitative research. In collecting the data, this study used a questionnaire consisting of emotional intelligence and motivation variables. While the data of students achievement variables was obtained from the results of the students' test scores. While the techniques used to test hypotheses was path analysis with the technique of multiple linear regression analysis. The result of the data analysis proved that (1) emotional intelligence possessed by the students was high, the learning motivation was classified as very high, and students achievement was also high, (2) there was relationship between emotional intelligence and learning motivation, that the significance of the t-test value was 0.012, (3) there was relationship between learning motivation and learning achievement, the significance of the t-test value was 0.007, (4) there was simultaneous relationship between emotional intelligence and students learning motivation which was described by the significance value of F test that was 0.000. Whereas the scale of relationship between emotional intelligence and learning motivation was 65.5%, while 35.5% of which were influenced and related to other variables or by other factors that was not included in this research model, such as: the physical condition of the children, the learning environment, parental upbringing, etc. Moreover, as shown by the results of the ANOVA test, the significance value of R square was 0.682. The scale of direct relationship between Emotional intelligence and the students achievement was 0.012, and the scale of direct relationship between learning motivation and learning achievement of the students was 0.007. While the value of indirect relationship between emotional intelligence and students achievement was at 0.337 and the indirect relationship between learning motivation and learning achievement of the students was 0.360.This study tried to reveal the relationship between emotionalintelligence and learning motivation, the relationship between learningmotivation and students achievement, and to explain the direct and indirectrelationships between emotional intelligence and learning motivation with thestudents achievement. In accordance with the theme, this study is acorrelational quantitative research. In collecting the data, this study used aquestionnaire consisting of emotional intelligence and motivation variables.While the data of students achievement variables was obtained from the resultsof the students' test scores. While the techniques used to test hypotheses waspath analysis with the technique of multiple linear regression analysis. The result of the data analysis proved that (1) emotional intelligencepossessed by the students was high, the learning motivation was classified asvery high, and students achievement was also high, (2) there was relationshipbetween emotional intelligence and learning motivation, that the significance ofthe t-test value was 0.012, (3) there was relationship between learningmotivation and learning achievement, the significance of the t-test value was0.007, (4) there was simultaneous relationship between emotional intelligenceand students learning motivation which was described by the significance valueof F test that was 0.000. Whereas the scale of relationship between emotionalintelligence and learning motivation was 65.5%, while 35.5% of which wereinfluenced and related to other variables or by other factors that was notincluded in this research model, such as: the physical condition of the children,the learning environment, parental upbringing, etc. Moreover, as shown by theresults of the ANOVA test, the significance value of R square was 0.682. Thescale of direct relationship between Emotional intelligence and the studentsachievement was 0.012, and the scale of direct relationship between learningmotivation and learning achievement of the students was 0.007. While the valueof indirect relationship between emotional intelligence and studentsachievement was at 0.337 and the indirect relationship between learningmotivation and learning achievement of the students was 0.360.